High detection rate of azole-resistant Aspergillus fumigatus after treatment with azole antifungal drugs among patients with chronic pulmonary aspergillosis in a single hospital setting with low azole resistance. (9th July 2020) - Takeda, Keita; Suzuki, Junko; Watanabe, Akira; Arai, Teppei; Koiwa, Tomohiro; Shinfuku, Kyota; Narumoto, Osamu; Kawashima, Masahiro; Fukami, Takeshi; Tamura, Atsuhisa; Nagai, Hideaki; Matsui, Hirotoshi; et al.
Abstract: The prevalence of azole-resistant Aspergillus fumigatus (ARAF) among chronic pulmonary aspergillosis (CPA) patients treated with azoles in Japan is unknown. The aim of this study was to determine the detection rate of ARAF in isolates from CPA patients who were treated with azoles for varying durations. The potential mechanism of acquiring resistance was examined by sequencing cyp51A and hmg1, two genes associated with ARAF. A. fumigatus isolates ( n  = 120) were collected from CPA patients ( n  = 104) between February 2012 and February 2019, at National Hospital Organization Tokyo National Hospital. The isolates were tested for susceptibility to the azole drugs itraconazole (ITCZ) and voriconazole (VRCZ). The detection rate of ARAF among all isolates was 8.3% ( n  = 10). Of the 10 resistant isolates, eight were ITCZ-resistant and five were VRCZ-resistant. Among 47 isolates obtained from 36 CPA patients who were treated with ITCZ (for an average of 256 days) and/or VRCZ (for an average of 29 days), the resistance rates were 17.0% and 10.6%, respectively. In addition, 46.2% of 13 isolates obtained from CPA patients with ongoing azole treatment at the time of antifungal therapy failure were resistant to azoles. Among the 10 ARAF isolates, a point mutation was detected in cyp51A in seven isolates and in hmg1 in two isolates. ARAF was detected at a high rate in CPA patients, particularly in those with ongoing long-term azole treatment, at the time of azole antifungal therapy failure. Lay Summary: Aspergillus fumigatus can acquire azole resistance during long-term treatment with azole drugs in patients with chronic pulmonary aspergillosis (CPA). The aim of this study was to determine the detection rate of azole-resistant A. fumigatus (ARAF) in isolates from CPA patients who had been treated with azoles. In addition, a potential mechanism of acquiring resistance was examined by sequencing cyp51A and hmg1, two genes associated with ARAF. A. fumigatus isolates ( n  = 120) were collected from CPA patients ( n  = 104). The isolates were tested for susceptibility to the azole drugs itraconazole (ITCZ) and voriconazole (VRCZ). The detection rate of ARAF from all isolates was 8.3% ( n  = 10). Greater than 10% of the 47 isolates obtained from 36 CPA patients who had been treated with azoles exhibited resistance. Furthermore, 46.2% of 13 isolates obtained from CPA patients with ongoing azole treatment at the time of antifungal therapy failure were resistant to azoles. Among the 10 ARAF isolates, a point mutation was detected in cyp51A in seven isolates and in hmg1 in two isolates. ARAF was detected at a high rate in CPA patients undergoing long-term azole treatment at the time of antifungal therapy failure.